A charge sensor integration to tunable double quantum dots on two neighboring InAs nanowires. Issue 2 (4th January 2021) - Wang, Xumin; Huang, Shaoyun; Wang, Ji-Yin; Pan, Dong; Zhao, Jianhua; Xu, H. Q.
Abstract : A charge sensor is integrated to scalable double quantum dots on two neighboring InAs nanowires. Abstract : A single quantum dot serving as a charge sensor is integrated to scalable double quantum dots using local top finger-gate techniques on two neighboring pure-phase InAs nanowires. The single dot built on one nanowire capacitively couples one of the double dots constructed on another nanowire via a metal bridge gate. The charge occupation states of double quantum dots can be accurately monitored by the sensor even in a few-electron regime in which transport tunneling current through the double dots vanishes. In the tunneling spectroscopy of double dots, electron inter dot tunneling process is absent; however, it can be illustrated by the sensor in terms of a transconductance line between the two closest triple points. Thus, tunnel coupling strength between the double dots is quantitatively extracted from the detectable charge transition. The highly tunable multiple quantum dots with integrated charge sensors on InAs nanowires could be an essential building block for quantum information processing technology.